2015
DOI: 10.1037/tep0000083
|View full text |Cite
|
Sign up to set email alerts
|

Provision of evidence-based therapies to rural survivors of domestic violence and sexual assault via telehealth: Treatment outcomes and clinical training benefits.

Abstract: Rural survivors of sexual assault and domestic violence experience considerable difficulties accessing mental health services. Similarly, graduate psychology training programs located in rural locations have historically been limited in their ability to provide trainees with extensive exposure to specific client populations. With the advent of distal technologies-especially secure, encrypted videoconferencing capabilities-it is now possible to connect rural clients with specialized, mental health services prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…A study conducted by Germain et al [ 67 ] with 46 participants showed that the sample did not present any significant difference in establishing TA. Gray et al [ 68 ], in a preliminary study on people living in a rural area, highlighted a positive response from psychologists, crisis center staff, and clients. The same result of feasibility and safety has been noticed by Acierno et al [ 69 ] with a large sample of veterans.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by Germain et al [ 67 ] with 46 participants showed that the sample did not present any significant difference in establishing TA. Gray et al [ 68 ], in a preliminary study on people living in a rural area, highlighted a positive response from psychologists, crisis center staff, and clients. The same result of feasibility and safety has been noticed by Acierno et al [ 69 ] with a large sample of veterans.…”
Section: Resultsmentioning
confidence: 99%
“…This search yielded results primarily related to medical provider satisfaction with telemedicine or telepsychiatry services (Becevic, Boren, Mutrux, Shah, & Banerjee, ; Hicks, Fleming, & Desaulnier, ; Jacobson & Hooke, ; Kobb, Hoffman, Lodge, & Kline, ; Sandberg et al, ; Savin, Garry, Zuccaro, & Novins, ). Of the two studies that examined TMH in a broader scope, the findings were mixed: one study described high satisfaction of clinical psychology trainees when providing TMH to domestic violence and sexual assault survivors (Gray et al, ) and the other study indicated that neuropsychologists reported lower satisfaction ratings of psychodiagnostic interviews performed via CVT when compared with interviews performed in person (Schopp, Johnstone, & Merrell, ). Research specific to TMH utilization in a mental health setting has generally focused on the potential use of this technology (Perle, Burt, & Higgins, ) or the perceived barriers experienced by providers with minimal to no experience in use of the technology in practice (Adler, Pritchett, Kauth, & Nadorff, ; Gibson et al, ; Simms, Gibson, & O'Donnell, ).…”
Section: Introductionmentioning
confidence: 99%
“…Research on the treatment of PTSD via telehealth is growing and findings are encouraging . Exploring ways to reduce barriers and improve access for women and ethnic minorities is an especially valuable element of telehealth . The current study adds to existing literature by examining the application of COPE via telehealth to treat a female minority U.S. military veteran with PTSD and alcohol use disorder (AUD).…”
Section: Introductionmentioning
confidence: 99%